"At the Threshold of Silence": Le Corbusier, "Le Parthénon, " and the Vision of Antiquity. Issue 4 (18th November 2021) - Guerra, Andrea
Abstract: In 1914, three years after his visit to the Acropolis in Athens during his travels through the East, Le Corbusier wrote "Le Parthénon, " the penultimate chapter in the diary published posthumously in 1966 under the title Voyage d'Orient . The text, studied here from the original 1914 manuscript, is distinctive in that it attenuates the journalistic style prevalent in other chapters of Voyage to express considerations on artistic creation and the meaning of making architecture. The analysis reveals a powerful visionary component, inspired by images borrowed from painting and literature that would leave indelible traces in Le Corbusier's poetics.